A comprehensive evaluation of the transition to a biosimilar of adalimumab in rheumatoid arthritis and psoriatic arthritis: a single-center experience with a focus on imaging outcomes - Rodrigo Garcia-Salinas; Sebastian Magri; Alvaro Ruta; Santiago Ruta (Reumatismo)
Objective. Limited data in Latin America exists regarding the efficacy of switches from original biologicals to biosimilars in real-life scenarios. Currently, no studies assess this switch using imaging. The objective of this study was to evaluate clinical, functional, ultrasonographic, and radiological responses in a group of patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) switched from original adalimumab (oADA) to biosimilar (bADA) (GP2017).